Analisis Praktik Bagi Hasil dalam Gaduh Kambing Perspektif Hukum Ekonomi Syariah - Aji Ramadhoni; Eti Karini; Herlina Kurniati (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Goat rowing is a cooperation between two parties, the owner and the keeper of the goat, where the owner hands over the goat to the keeper to be kept. This research method is a field research with a descriptive qualitative approach because it explains the actual state of the research unit that produces descriptive data in the form of words and observable behaviors. The system of sharing the results obtained from the results of goat managers (goat rowing) is obtained without calculating the costs incurred by goat farmers in the goat rowing business. With a profit distribution of 50:50 after deducting the initial capital where it has been agreed and after the initial contract. The goat farming business in Tatakarya Village, Abung District, Surakarta, North Lampung, uses the paro system is still not fully in accordance with the principle of mudharabah. The results of the discovery of risks and losses experienced in the cooperation process where if there are livestock that die is the responsibility of the animal owner. In general, the practice carried out with the mudharabah (cooperation) contract shows the contract, capital and the concept of profit sharing (profit making). In addition, in the principles of sharia that must be fulfilled 1) The Principle of Justice (Al-'Adl), 2) The Principle of Willingness (An-Taradhin), 3) The Principle of Clarity (Gharar), 4) Trust, 5) The Principle of No Harm (La Dharar wa La)